Acetylated KIAA1429 by TIP60 facilitates metastasis and immune evasion of hepatocellular carcinoma via N6-methyladenosine-KDM5B-mediated regulation of FoxO1 - Hu Quan; Huijun Zhou; Fei Chen; Jie Chen; Yun He; Hua Xiao; Jia Liu; Lei Shi; Wei Xie; Pan Chen; Jia Luo (Cell Death Discovery)
Abstract Hepatocellular carcinoma (HCC) is characterized by programmed cell death ligand-1 (PD-L1)-mediated immune escape. This study aimed to elucidate the function and mechanism behind KIAA1429, a component of N6-methyladenosine (m6A) complex, in immune escape of HCC. PD-L1 expression was assessed through immunofluorescence staining, and flow cytometry was used to determine CD8+ T cell percentage. The level of IFN-γ was detected using enzyme-linked immunosorbent assay. Cell proliferation, migration, and invasion were evaluated through CCK-8, colony formation, and Transwell assays, respectively. The m6A modification level was measured using an RNA methylation quantification assay, m6A dot blot, and methylated RNA immunoprecipitation-qPCR. Molecule interaction was validated using RNA pulldown, RNA immunoprecipitation, chromatin immunoprecipitation, and co-immunoprecipitation assays. In vivo HCC growth was evaluated in NOD/SCID mice. We found that TIP60, KIAA1429 and KDM5B were highly expressed in HCC cells, while FoxO1 was poorly expressed. Functionally, TIP60/KIAA1429 silencing inhibited PD-L1-mediated HCC immune evasion, growth, migration, and invasion. Mechanistically, TIP60 led to acetylation of KIAA1429, which promoted KDM5B expression in an m6A-YTHDF1-dependent manner, and subsequently restrained the transcription and expression of FoxO1. Enforcing YTHDF1 expression or depleting FoxO1 expression markedly reversed the suppressive effect of shKIAA1429 on HCC immune evasion, growth, migration, and invasion. Overall, these findings suggest that acetylated KIAA1429-mediated m6A modification endows HCC cells with immune evasion through regulation of KDM5B/FoxO1 axis, which provide a treatment option for HCC by targeting KIAA1429.